Round table. Tactics and techniques in pancreas surgery: coordinador Oscar Bermúdez; integrantes Dres Bolívar Delgado, Rafael García Capurro, Roberto Grezzi, José Ma. Mainetti, Raúl Praderi, Jorge C. Pradines - Bermúdez, Oscar (Cirugía del Uruguay, 1971)
The subject that we will develop has been repeatedly proposed by the congressmen to be discussed in the Round Table. "Surgery of the pancreas" considered globally is a very broad topic, impossible to fully develop in a Round Table. We have selected the technical and tactical aspects most useful to the surgeon general, circumscribed to three sectors of the pathology of the organ: 1) Surgery of malignant tumors (cephalopancreatic proper, vaterian tumors, corporocaudal and flows). 2) Surgery for cystic processes (cysts themselves, pseudocysts and cystic tumors). 3) Surgical resources in chronic pancreopathies.